(untitled) (Confluenţe Bibliologice, 2013)
The author describes the life and works of the famous French encyclopedist Pierre Larouss, also known as educator, lexicographer and editor. He was born in Toucy (Yonne) in October 23, 1817 and died in Paris on 3 January, 1875. He was concerned about the methods of education in French language. Since 1849 he wrote many pedagogical works. In 1852 Pierre Larouss established Larousse Librairie, together with Augustin Boyer, who would become famous thanks to the works published by him.